2023
DOI: 10.1002/adfm.202303009
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible and Safe Planar Zinc‐Ion Micro‐Battery with Ultrahigh Energy Density Enabled by Interfacial Engineering for Wearable Sensing Systems

Abstract: Aqueous zinc-ion micro-batteries (ZIMBs) have attracted considerable attention owing to their reliable safety, low cost, and great potential for wearable devices. However, current ZIMBs still suffer from various critical issues, including short cycle life, poor mechanical stability, and inadequate energy density. Herein, the fabrication of flexible planar ZIMBs with ultrahigh energy density by interfacial engineering in the screen-printing process based on highperformance MnO 2 -based cathode materials is repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…At 0.3 mA cm –2 , areal device capacities reached 4.82, 7.93, and 11.93 mA h cm –2 for 1, 2, and 3 printing layers, respectively. The achieved device capacity values were superior to those of most reported Zn-based battery devices and even Li-based battery devices. It can be observed that the 3DP-NiVO//NHCs@Zn battery exhibited a high energy density of up to 5.98 mW h cm –2 , which was superior to those of reported micro energy storage devices (Figure d). ,, …”
Section: Resultsmentioning
confidence: 86%
“…At 0.3 mA cm –2 , areal device capacities reached 4.82, 7.93, and 11.93 mA h cm –2 for 1, 2, and 3 printing layers, respectively. The achieved device capacity values were superior to those of most reported Zn-based battery devices and even Li-based battery devices. It can be observed that the 3DP-NiVO//NHCs@Zn battery exhibited a high energy density of up to 5.98 mW h cm –2 , which was superior to those of reported micro energy storage devices (Figure d). ,, …”
Section: Resultsmentioning
confidence: 86%
“…3d), one pair of redox peak corresponding to the MnO 2 /MnOOH conversion reaction could be found in the Zn/MnO 2 battery with two types of electrolytes, which was consistent with the charge/discharge plateaus in galvanostatic charge/discharge curves (GCDs). 30–32 Meanwhile, the higher current density of Zn/MnO 2 batteries with Ce(SO 4 ) 2 additives in comparison with that without Ce(SO 4 ) 2 additives indicated a higher specific capacity, which was ascribed to the dynamic compensation mechanism (Fig. 3e–g).…”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, planar micro batteries are smaller and lighter in size and weight and more flexible, making them easier to wear to supply energy for wearable electronic devices (Figure 5f). 49 The preparation process of planar microcells usually involves the printing of highly conductive substances with inert properties as current collectors, such as graphene, Ag, Au, etc., in specific pattern onto flexible substrates (e.g., polyethylene terephthalate, PET) by screen printing. Subsequently, the inks containing the active material are printed on the cathodic and anodic current collectors, respectively, and then the electrolyte is added and the battery is encapsulated.…”
Section: ■ Aqueous Battery For Wearable Electronic Devicesmentioning
confidence: 99%
“…This also allows the electrode shape of the micro battery to be designed arbitrarily, providing an opportunity for the development of high-performance micro batteries. Meanwhile, planar micro batteries are smaller and lighter in size and weight and more flexible, making them easier to wear to supply energy for wearable electronic devices (Figure f) . The preparation process of planar microcells usually involves the printing of highly conductive substances with inert properties as current collectors, such as graphene, Ag, Au, etc., in specific pattern onto flexible substrates (e.g., polyethylene terephthalate, PET) by screen printing.…”
Section: Aqueous Battery For Wearable Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation